Controlling the Quality of Nanodrugs According to Their New Property-Radiothermal Emission - Gleb V. Petrov; Daria A. Galkina; Alena M. Koldina; Tatiana V. Grebennikova; Olesya V. Eliseeva; Yana Yu. Chernoryzh; Varvara V. Lebedeva; Anton V. Syroeshkin (MDPI AG, 2024)
Previous studies have shown that complexly shaped nanoparticles (NPs) have their intrinsic radiothermal emission in the millimeter range. This article presents a method for controlling the quality of nanodrugs-immunobiological preparations (IBPs)-based on the detection of their intrinsic radiothermal emissions. The emissivity of interferon (IFN) medicals, determined without opening the primary package, is as follows (µW/m2): IFN-α2b-80 ± 9 (105 IU per package), IFN-β1a-40 ± 5 (24 × 106 IU per package), IFN-γ-30 ± 4 (105 IU per package). The emissivity of virus-like particles (VLP), determined using vaccines Gam-VLP-multivac (120 μg) in an injection bottle (crimp cap vials), was as follows: 12 ± 1 µW/m2, Gam-VLP-rota vaccines-9 ± 1 µW/m2. This study shows the reproducibility of emissivity over the course of a year, subject to the storage conditions of the immunobiological products. It has been shown that accelerated aging and a longer shelf life are accompanied by the coagulation of active NPs, and lead to a manyfold drop in emissivity. The dependence of radiothermal emission on temperature has a complex, non-monotonic nature. The emission intensity depends on the form of dosage, but remains within the order of magnitude for IFN-α2b for intranasal aqueous solution, ointments, and suppositories. The possibility of the remote quantitative control of the first phases of the immune response (increased synthesis of IFNs) to the intranasal administration of VLP vaccines has been demonstrated in experimental animals.